Brain GABA and Glutamate Concentrations Following Chronic Gabapentin Administration: A Convenience Sample Studied During Early Abstinence From Alcohol - Meyerhoff, Dieter J.; Murray, Donna E.; Durazzo, Timothy C.; Pennington, David L. (Frontiers in Psychiatry, 2018)
Gabapentin (GBP), a GABA analogue that may also affect glutamate (Glu) production, can normalize GABA and Glu tone during early abstinence from alcohol, effectively treating withdrawal symptoms and facilitating recovery. Using in-vivo magnetic resonance spectroscopy, we tested the degree to which daily GBP alters regional brain GABA and Glu levels in short-term abstinent alcohol dependent individuals. Regional metabolite levels were compared between 13 recently abstinent alcohol dependent individuals who had received daily GBP for at least 1 week (GBP+) and 25 matched alcohol dependent individuals who had not received GBP (GBP-). Magnetic resonance spectra from up to five different brain regions were analyzed to yield absolute GABA and Glu concentrations. GABA and Glu concentrations in the parieto-occipital cortex were not different between GBP- and GBP+. Glu levels in anterior cingulate cortex, dorsolateral prefrontal cortex, and basal ganglia did not differ between GBP- and GBP+. However, in a subgroup of individuals matched on age, sex, and abstinence duration, GBP+ had markedly lower Glu in the frontal white matter than GBP-, comparable to concentrations found in light/non-drinking controls. Furthermore, lower frontal white matter Glu in GBP+ correlated with a higher daily GBP dose. Daily GBP treatment at an average of 1600 mg/day for at least 1 week was not associated with altered cortical GABA and Glu concentrations during short-term abstinence from alcohol, but with lower Glu in frontal white matter. Gabapentin for the treatment of alcohol dependence may work through reducing Glu in white matter rather than increasing cortical GABA.